Analisis Perbedaan Prestasi Belajar Mahasiswa Fakultas Tarbiyah Dan Ilmu Keguruan (Ftik) Iain Palu Pada Mata Kuliah Evaluasi Pembelajaran Berdasarkan Gender - Mistiani, Wiwin (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
This study aims to determine the student achievement of male and female students on the subyek Evaluation of learning and to determine of Differences in student achievement FTIK IAIN Palu on the subject evaluastion learning by gender. The approach used is descriptive quantitative. While the population in this study are all students. The sampling technique is done by using proportional random sampling technique. With the number of students 60 people then the sample = 37 students of FTIK IAIN Palu. Technique of collecting data by using test and observation while data analysis using T test.From the research, 1) the average of learning achievement in the subject of male students' learning appraisal from 19 male students who are the sample in this research is 79,42 means good category. Meanwhile, from 18 female students who became the sample of the study, the average of learning achievement in the subject of female students' learning evaluation is 77 means either. 2) There is no significant difference Student Learning Achievement FTIK) IAIN Palu On the subject Evaluation Learning Based on Gender with t value equal to = 0,0267 with t table with dk 35 with error level 5% is 0,062.